2010
DOI: 10.1007/s00128-010-0056-3
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 Contamination in Raw Milk within the Central Region of Thailand

Abstract: Aflatoxin M(1) (AFM(1)) was found in all of the 240 raw milk samples collected from milk tanks of 80 dairy farms at a collecting center in the central region of Thailand. Milk samples from individual farms were collected in three seasons. The average concentration of AFM(1) in milk samples collected in winter (0.089 +/- 0.034 microg/L) was significantly higher than those in rainy season (0.071 +/- 0.028 microg/L) and summer (0.050 +/- 0.021 microg/L). The present study suggests that regulatory limits for AFM(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 7 publications
4
17
1
Order By: Relevance
“…No comparative data on AFM 1 excreted during morning or evening lactation was found in the literature. However the concentrations of AFM 1 in milk samples were comparable with previous results from Pakistan and other countries as shown in Table 4 (Fallah, 2010;Rahimi, Shakerian, Jafariyan, Ebrahimi, & Riahi, 2009;Ruangwises & Ruangwises, 2010). However, lower levels of AFM 1 contamination have been reported in some studies (Biland zi c, Varenina, & Solomun, 2010;Bognanno et al, 2006;Boudra et al, 2007;Diaz & Espitia, 2006;Motawee et al, 2009;Nakajima et al, 2004;Pei, Zhang, Eremin, & Lee, 2009).…”
Section: Resultssupporting
confidence: 92%
“…No comparative data on AFM 1 excreted during morning or evening lactation was found in the literature. However the concentrations of AFM 1 in milk samples were comparable with previous results from Pakistan and other countries as shown in Table 4 (Fallah, 2010;Rahimi, Shakerian, Jafariyan, Ebrahimi, & Riahi, 2009;Ruangwises & Ruangwises, 2010). However, lower levels of AFM 1 contamination have been reported in some studies (Biland zi c, Varenina, & Solomun, 2010;Bognanno et al, 2006;Boudra et al, 2007;Diaz & Espitia, 2006;Motawee et al, 2009;Nakajima et al, 2004;Pei, Zhang, Eremin, & Lee, 2009).…”
Section: Resultssupporting
confidence: 92%
“…Thailand is one of several countries that have not yet established regulatory limits for AFM 1 in raw milk and milk products. The present study and our two previous reports (Ruangwises & Ruangwises, 2009, 2010 suggest regular monitoring of raw milk and milk products, and regulatory limits for AFM 1 to ensure the quality of raw milk and milk products in Thailand. …”
Section: Resultssupporting
confidence: 66%
“…Blanco et al (1988) andEl Marnissi et al (2012) found high contamination in milk samples collected in autumn; Diaz & Espitia (2006) found the highest AFM1 concentration predominantly in the rainy season; Markaki & Melissari (1997) and Rodriguez, Calonge & Ordonez (2003) reported no seasonal influence on the aflatoxin content in the milk samples they analyzed. Panariti (2001), Tajkarimi et al (2007;, Hussain & Anwar (2008), Ozsunar, Gumus, Arici & Demirci (2010), Nemati, Mehran, Hamed & Masoud (2010), Heshmati & Milani (2010), Ruangwises & Ruangwises (2010) and Iqbal, Asi & Jinap (2013) have found higher AFM1 concentrations in winter compared with other seasons. Most of the authors presumed that the marked higher contamination of AFB1 in foodstuffs during winter could be a result of the feed, consisting mainly of stored foodstuff, sometimes keep under humid conditions and thereby facilitating the growth of fungi and accumulation of toxins.…”
Section: Seasonal Changes In Afm1 Concentrations In Milkmentioning
confidence: 99%